Synchronous Learning with STEM and Economics Students’ Critical Thinking Abilities - Bagus Shandy Narmaditya; Yuli Agustina; Sri Handayani; Lisa Rokhmani; Prih Hardinto; Syahrul Munir; Yohanes Hadi Soesilo; M. Rudi Irwansyah (Universitas Negeri Malang, 2021)
Increasing the quality of education has been a global challenge. The Indonesian government has responded this issue by reforming new curriculum that focuses on students’ activities and critical thinking ability. This study aims at investigating the implementation of synchronous learning with STEM and its impact to students’ critical thinking ability. This research adopted mixed methods, quasi-experimentally by using non-equivalent control group design research to gain a deeper understanding during experiment. The result of this work notes that synchronous learning with STEM slightly out performs the conventional learning activities and it can moderately illustrate the enhancing of students’ critical thinking skills. The introduction of STEM in social sciences, primarily in an economics course, faces some challenges and adjustments as well as its implementation using live synchronous learning This result suggests to more comprehensive planning and materials in adopting STEM in social sciences as well as an effort to increase students’ activities.Keywords: Critical Thinking Skills, STEM Education, Economics Students, Synchronous Learning